Antimelanoma differentiation-associated gene 5 (anti-MDA5) antibody-positive dermatomyositis: clinical features and outcomes in a racially diverse patient cohort - Sai K. Koyoda; Fatema Ezzy; Dawn Wahezi; Anand Kumthekar; Xianhong Xie; Clement E. Tagoe; Bibi Ayesha (BMC Rheumatology)
Abstract Background The anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody-positive dermatomyositis is known for its association with rapidly progressive interstitial lung disease (RP-ILD) and ulcerative skin lesions, often presenting with or without muscle involvement. The aim of this study was to identify distinct clinical and laboratory features that could be used to evaluate disease progression in an ethnically diverse cohort of anti-MDA5 dermatomyositis patients at a U.S. academic center. Methods A retrospective chart review was conducted on dermatomyositis patients hospitalized at our institution between January 2014 and June 2023. The data were analyzed via Fischer’s exact test and a t test. Results Among the 195 dermatomyositis patients reviewed, 22 tested positive for the MDA5 antibody, comprising of thirteen adults and nine pediatric patients. Myositis was significantly more common in pediatric patients than in adult patients (p = 0.002). RP-ILD was more frequently observed in adult patients of African ancestry (including both Black Hispanic and Black non-Hispanic individuals) (p = 0.04). There was a significant association noted between Raynaud’s phenomenon and ILD (p = 0.02). The overall mortality rate of 13.6% was more favorable than the previously reported rates of 40–60%. Conclusion This study enhances our understanding of the disease by emphasizing potential racial and demographic variations, as well as delineating the similarities and differences between adult and pediatric populations.